An analytical tool to support the pedestrianisation process: The case of via Roma, Cagliari - Annunziata, Alfonso; Pisano, Carlo (TeMA - Journal of Land Use, Mobility and Environment, 2018)
The article focuses on the case of the modification of an urban road network: the transformation of a portion of an important distributor road in the urban area of Cagliari into a pedestrian space. By means of this case study the article aims to point out how pedestrianisation interventions have not been completely defined within a theoretical system that clearly establishes modes and conditions of implementation. This lack of theorization has led to the common understanding of pedestrianisation as good operations in and of itself and, as such, exportable, meant to produce the same effects everywhere (Bianchetti, 2016). This analysis uses the fundamental conditions of hierarchy as a tool to assess to what extent the modification of the road network articulation has resulted in conditions of lesser inter-connectivity, legibility and functionality. In this perspective the article proposes a system of criteria, founded on the principles of hierarchy, meant to be a theoretical support for processes of pedestrianisation.